2022
DOI: 10.1038/s41586-022-05266-z
|View full text |Cite
|
Sign up to set email alerts
|

Gut–brain circuits for fat preference

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…In accordance, we found that SucrW 12Wk feeding increased AgRP neuronal activity and caloric intake without significantly altering bodyweight or body composition. These changes in neuronal firing mirror HFDinduced changes to AgRP neuronal firing rate in DIO mice [24,31], though to a lesser extent, likely driven by functional differences in fat-and sugar-sensitive afferents to the hypothalamus and AgRP neurons [33][34][35]77] or even disparate circuitries for hedonic and nutritional sugar preference [40]. Interestingly, fasting failed to further increase the F AP of AgRP neurons suggesting that (1) AgRP neurons are refractory to additional relevant stimuli, or (2) this rate represents a ceiling beyond which AgRP neurons are not able to sustain action potential firing.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In accordance, we found that SucrW 12Wk feeding increased AgRP neuronal activity and caloric intake without significantly altering bodyweight or body composition. These changes in neuronal firing mirror HFDinduced changes to AgRP neuronal firing rate in DIO mice [24,31], though to a lesser extent, likely driven by functional differences in fat-and sugar-sensitive afferents to the hypothalamus and AgRP neurons [33][34][35]77] or even disparate circuitries for hedonic and nutritional sugar preference [40]. Interestingly, fasting failed to further increase the F AP of AgRP neurons suggesting that (1) AgRP neurons are refractory to additional relevant stimuli, or (2) this rate represents a ceiling beyond which AgRP neurons are not able to sustain action potential firing.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, we and others have recently described acute and long-term synaptic mechanisms [31] that mediate AgRP neuronal hyperactivity ex vivo [24,28] and postprandial desensitization identified by in vivo calcium imaging studies [29,30]. While recent studies have identified distinct gut-brain pathways for fat and sugar signaling to AgRP/NPY neurons [33][34][35] the longterm influence of high dietary sucrose consumption on AgRP neuronal function, plasticity, and body weight has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, we found that SucrW 12Wk feeding increased AgRP neuronal activity and caloric intake without signi cantly altering bodyweight or body composition. These changes in neuronal ring mirror HFD-induced changes to AgRP neuronal ring rate in DIO mice [25,29], though to a lesser extent, likely driven by functional differences in fat-and sugar-sensitive afferents to the hypothalamus and AgRP neurons [33][34][35]63] or even disparate circuitries for hedonic and nutritional sugar preference [40]. Additionally, synaptic plasticity of excitatory and inhibitory inputs to AgRP neurons in lean SucrW 12Wk mice were akin to DIO HFD 8Wk fed mice [29].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, we and others have recently described acute and long-term synaptic mechanisms [29] that mediate AgRP neuronal hyperactivity ex vivo [25,28] and postprandial desensitization identi ed by in vivo calcium imaging studies [30,31]. While recent studies have identi ed distinct gut-brain pathways for fat and sugar signaling to AgRP/NPY neurons [33][34][35] the long-term in uence of high dietary sucrose consumption on AgRP neuronal function, plasticity, and body weight has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…These cells have polarity and chemoreceptors on luminal side detect specific class of nutrients and cause secretion of peptides on the basolateral side ( Gutierrez-Aguilar and Woods, 2011 ). By using knockout animals and functional imaging of the nodose ganglion, Li et al proved preference of sugar and fat ingestion is controlled by gut-brain axis via intestinal stimulation of receptors on gut epithelium and vagal nerve transmission, in which SGLT-1 controls sugar preference while GPR40/GPR120 are the essential mediators of intestinal fat signals to the vagal neurons ( Li et al, 2022 ). Distribution of glucose sensors on enteroendocrine L-cells and the molecular mechanism involved in the regulation of GLP-1 secretion are well understood.…”
Section: Location Of Gpr40 Protein On Enteroendocrine L-cells—luminal...mentioning
confidence: 99%